Hindu Tantric Practices of Kathmandu Valley - Baid , Kanav (HISAN: Journal of History Association of Nepal, 2025)
Tantric Practices in Nepal have formed the bedrock of Nepali culture and have shaped Nepal profoundly. This research article has been formed to specifically outline and shed light on the various tantric practices that are in use in the Kathmandu Valley. It discusses the anthropological origins of this form of Hinduism, its mythology and pantheon, as well as its daily practices and some of its core philosophical concepts. We discuss its origins with the idea of the “divine feminine” or Shakti, and we also recognize the hand tantric practices that have played in shaping the Kathmandu Valley, the various Mahaviyas as well as the ashtmatrikas.